2000
DOI: 10.1002/1097-4644(20001215)79:4<576::aid-jcb60>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Fully processed lysyl oxidase catalyst translocates from the extracellular space into nuclei of aortic smooth-muscle cells

Abstract: Lysyl oxidase (LO), a secreted protein, was recently identified within the nuclei of vascular smooth-muscle cells (SMC) and 3T3 fibroblasts. A possible pathway by which LO can enter cell nuclei was explored in the present study. SMC were incubated with purified 32-kDa bovine aorta LO that had been fluorescently labeled with rhodamine (TRITC-LO). TRITC-LO entered the cytosol and then rapidly concentrated within the nuclei of preconfluent cultures of these cells, whereas carbonic anhydrase, a protein of similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
51
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 28 publications
4
51
1
Order By: Relevance
“…LOX enters the cells and moves into nuclei in a manner that appears to be independent of its catalytic activity, as previously reported [49]. In this study, LOX-positive gastric cancer was found to be associated with tumor cell invasion, Lysyl oxidase is associated with the epithelial-mesenchymal transition of gastric cancer… 439 lymph node metastasis, lymphatic invasion, venous invasion, and peritoneal dissemination.…”
Section: Discussionsupporting
confidence: 81%
“…LOX enters the cells and moves into nuclei in a manner that appears to be independent of its catalytic activity, as previously reported [49]. In this study, LOX-positive gastric cancer was found to be associated with tumor cell invasion, Lysyl oxidase is associated with the epithelial-mesenchymal transition of gastric cancer… 439 lymph node metastasis, lymphatic invasion, venous invasion, and peritoneal dissemination.…”
Section: Discussionsupporting
confidence: 81%
“…Kagan et al first documented the presence and retained catalytic activity of LOX mature enzyme within the nuclei of rat vascular smooth muscle cells and NIH 3T3 fibroblasts [23]. Later, it was demonstrated that exogenous mature LOX enzyme could enter the cells and concentrate within the nuclei [24]. Here for the first time, our results demonstrated the existence of LOX proenzyme (50kDa) and mature enzyme (32kDa) within the nuclei of colon cancer cells.…”
Section: Discussionsupporting
confidence: 62%
“…Mature lysyl oxidase enzyme has been reported to be taken up by cells and translocated to the nucleus of some cells, where it influences the transcription of type III collagen (67)(68)(69). It has been suggested that lysyl oxidase could interact with histones (70), known in vitro substrates of purified lysyl oxidase (71), and thereby possibly directly or indirectly regulate gene transcription.…”
Section: Discussionmentioning
confidence: 99%